Free Radical Scavenging Activity of Betalaine of Beta vulgaris - Babu V.L., Ashoka; Banu, Shanaz; R., Dhanapal; Swamy B.M., Vrushabendra; Kumar, G.S.; Chandanam, Sridhar (Asian Journal of Chemistry, 2010)
The present study deals with the antioxidant potential of betalaines. The acidified aqueous extract of the plant (root) was investigated for in vivo effect on the production of body enzymes, i.e., catalase and superoxide dismutase. The extract has shown significant antioxidant activity.